Effectiveness of Sleep-Based Cognitive Behavioral Interventions on Emotion Regulation and Sleep Quality in Children Aged 7 to 12 with Combined Type Attention-Deficit/Hyperactivity Disorder - Ghods Hosseini, Sarasadat; Shariat Bagheri, Mohamad Mahdi; Tajali, Parisa (Iranian Journal of Neurodevelopmental Disorders, 2026)
Purpose: The present study aimed to investigate the effect of sleep-based cognitive behavioral interventions on children aged 7 to 12 with combined type attention-deficit/hyperactivity disorder (ADHD) regarding emotion regulation and sleep quality. This study examined the impact of these interventions on two primary domains: emotion regulation and ADHD/hyperactivity symptoms.Methods and Materials: This experimental study employed a pretest-posttest design. Participants included 34 children diagnosed with ADHD (17 per group) who received sleep-based cognitive behavioral interventions. Data were collected using standardized instruments, including the Emotion Regulation Checklist – Parent Form (Shields & Cicchetti, 1995), the Pittsburgh Sleep Quality Index (PSQI) (Buysse et al., 1989), and the Conners’ Rating Scale (Conners, 2008). Analyses were conducted using analysis of covariance (ANCOVA) in SPSS version 26.Findings: Findings indicated that sleep-based cognitive behavioral interventions improved overall sleep quality and its associated components, enhanced satisfaction with sleep, and positively affected daytime functioning (p